Akselerasi Kinerja UMKM Desa Karyamekar, Kabupaten Garut Melalui Digitalisasi Manajemen SDM - Ria Estiana; Niantoro Niantoro; Akhwanul Akmal; Jaenudin Akhmad; Eko Sugiyanto (STIE Syariah Indonesia Purwakarta, 2026)
This community service research aims to address the managerial inefficiencies and vulnerability of Micro, Small, and Medium Enterprises (MSMEs) in Karyamekar Village, Garut, through the strengthening of Human Resources (HR) performance using Information Technology (IT). The main underlying problem is the conventional and manual HR management system, which leads to time-consuming administration and a lack of performance data transparency. The method employed was a Participatory Approach combined with Hands-on Technical Guidance involving 20 MSME owners. The technological intervention focused on utilizing simple mobile attendance applications and Google Sheets for digitalizing employee databases, matching the digital literacy capacity of the partners. The results show a significant 45% increase in theoretical HR management knowledge (post-test) and a high technology adoption rate of 85%. The conclusion indicates that digitalization in rural MSMEs relies less on expensive technology and more on knowledge transfer and the owners' willingness to adapt. This activity contributes to improving the professionalism of MSME human resource management through data-driven management practices, enhanced administrative efficiency, and strengthened transparency and internal trust, thereby supporting business sustainability and creating opportunities for program replication in rural MSMEs with similar characteristics. The main suggestion is the necessity for the Garut Local Government to provide stable digital infrastructure and support subsidized simple HRIS programs to ensure program sustainability.